Problems and trends in the storytelling activities of selected libraries with children's literature collection within Metro Manila - Salonga, Rochelle D.C., 1984- (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Viewing it significant to acquire more knowledge on storytelling a study on storytelling sessions in libraries with children's literature collection within Metro Manila was undertaken. The research aimed to identify the problems and trends in the three aspects of storytelling: the story, the storyteller, and the storytelling setting.